The beloved self morality and the challenge from egoism - Hills, Alison (Oxford : Oxford University Press, 2010)
'The Beloved Self' is about the holy grail of moral philosophy an argument against egoism that proves that we all have reasons to be moral. Hills suggests that egoism is not epistemically rational, offers a new theory of moral understanding, and examines the nature of moral action and the connection between what we should believe.
Description based on online resource; title from PDF title page (viewed on Sept. 7, 2010).
Includes bibliographical references and index.
Keywords: Ethics -- Psychological aspects; Egoism